The Motivation of Kang Jalal Keeping on Sufistic Thoughts - Muhammad Muhammad (Budapest International Research and Critics University, 2019)
The aims of this study is to find out the motivation of kang jalal keeping on sufistic thoughts. This study used qualitative research method. The result in this study shows that Kang Jalal's motivation to pursue Sufism was influenced by several factors: Psychological factors, preaching with Sufistic thinking; Sufistic ulama thought factor, Jalal likes to read Sufism literature; inter-school pro-counter factors, Jalal being neutral in thinking about differences between schools; the factor of spiritual crisis in modern society, it requires living comprehension, both vertically and horizontally, hablum minallah, hablum minannas and even hablum minal kauni perfectly.